The Cost of Export Subsidies : Evidence From Costa Rica - Hoffmaister, Willy (Washington, D.C. : International Monetary Fund, 1991)
This paper develops a model to estimate the effects of export subsidies on the supply of exports. Using data for Costa Rica over the 1980's, it is shown that while the export subsidy scheme in operation led to an increase in exports, the direct fiscal costs of the scheme were quite large. Furthermore, the subsidy scheme led to a significant increase of imports. These results suggest that elimination of export subsidies would not have a particularly harmful effect on the trade balance, and would increase the fiscal position and generate economic efficiency besides.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet